Relevansi Konsep Kafa'ah Menurut Zainuddin Bin Abdul Aziz Al-Malibary Dengan Konteks Kekinian - Asrori, Khozinatul; Mahfudz, Ahmad (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
In marriage, kafa’ah is often the subject of hot discussion. Jurisprudence studies in Indonesia are also inseparable from the influence of Al-Malibary whose works are studied in almost all Islamic boarding schools. This article aims to state its relation to the concept of kafa’ah offered by Zainuddin bin Abdul Aziz Al-Malibary in the context of today's society. This research is a library research with an analytical descriptive approach. The results of the study show that there are still criteria in kafa’ah which are no longer relevant, namely the hurriyah criteria. At least the criteria offered by Zainuddin bin Abdul Aziz Al-Malibary are religion and wealth. Apart from that, looking at the socio-cultural nature of today's society, it is necessary to have other criteria that must be considered in order to create a happy family, including criteria for education, health and maturity or mutual understanding of one another.